Health Problems Of Children And The Moral Resolve Of Adults - Alcabes, Philip (Research in the social scientific study of religion, 2008)
Children at Risk is a theme of modern American life, a set of claims that children’s behavior in the areas of drug use, diet, and sex are not merely potential health threats to some children but real pathologies to all. This essay argues that adults center our health concerns around children’s behavioral problems because we are uncomfortable with our own appetites, and lack the moral resolve to decide if we must protect children from them or teach them to deal with the world as it is. It demonstrates that American children are generally healthy, and not much in peril from unmanageable risks. It argues that adults’ insistence on childhood "innocence" deprives us of the capacity to take a nuanced and realistic look at children’s activities, instead expressing our moral irresolution. And it suggests that the lack of agreement over how children should be involved in research on health problems is a particularly pressing area where moral resolve is needed.